Teachers‘ Attitudes towards Using Cooperative Learning through Technology for Developing Writing Skills in a Military Context - Chkotua, Maia; Kharchilava, Maia (European Scientific Journal, ESJ, 2025)
Teachers of English for Specific Purposes (ESP) consider writing as one of the most difficult productive skills to teach military students. Writing is an essential skill for their future career development, as they must take the high-stakes STANAG 6001 (Standardisation Agreement 6001) test to be promoted. Teachers‘ role is pivotal in teaching ESP as they should take into account students‘ current needs and create goal-oriented assignments to develop their writing skills and improve their writing performance. Thus, the purpose of the study was to investigate ESP teachers’ attitudes towards using cooperative learning through technology for the development of writing skills, to examine their readiness for implementing the above-mentioned instructional strategy. The study used a quantitative method. The data was gathered from the teachers’ questionnaire and was analysed descriptively. Study participants were 58 teachers from different schools and several military educational institutions of North Atlantic Treaty Organisation (NATO) member, partner and candidate countries such as Ukraine, Latvia and the UK. SPSS 27 was used to analyse the data. The study results showed that the majority of ESP teachers had positive attitudes towards using cooperative learning through technology to develop writing skills.